Delineating and Operationalizing the Definition of Patient-Oriented Research: A Modified e-Delphi Study - Navdeep Kaur; Pierre Pluye (Journal of Patient-Centered Research and Reviews, 2019)
Purpose: The importance of patient-oriented research (POR) has been recognized by the scientific community and governmental agencies, and its development is exponential across most health-related disciplines. The current Canadian Institutes of Health Research (CIHR) definition of POR is overly broad and hinders the reliable selection of POR-related publications from bibliographic databases. The present study was aimed to adapt CIHR’s definition of POR into an operational definition that can be used by stakeholders for selecting POR publications. Methods: Eighteen POR experts in Québec, Canada, were invited to participate in a modified e-Delphi study. Two rounds of Delphi surveys were undertaken to reach consensus. Round-1 sought consensus on clarity and indispensability of POR characteristics. Round-2 included modifications planned in POR characteristics and obtained final consensus leading to an adapted POR definition. Finally, POR experts across Canada were consulted to assess generalizability of this adapted POR definition. Results: The item that achieved 75% of consensus was removal of the POR characteristic “POR can be conducted in partnership with relevant stakeholders,” because it was considered redundant and confusing. Additionally, participants suggested defining unclear concepts such as “continuum,” “direct impact,” and “patient.” Finally, based on results of Round-1 and Round-2 and the consultation with POR experts across Canada, an operational POR definition was developed. Conclusions: This study was a novel attempt to adapt an operational POR definition to help patients and POR stakeholders have a common understanding of what POR is, focus on important outcomes that matter to patients, and improve care quality.